Performance Reviewed from Transformational Leadership in SLB Teachers in Medan City - Hartini, Sri; Noviana Christina, Widya; Mona Gracia, Angeline Julia; Br Simanjorang, Christina Natalia; Manuel Sitinjak, David; Ika Putri, Nenny; stri Tarigan, Beby A; Lumbantoruan, Haposan (Jurnal Multidisiplin Indonesia, 2024)
Researchers conducted a study entitled Performance in Terms of Transformational Leadership on SLB Teachers in Medan City with a sample of 135 SLB teachers in Medan City. This study used purposive sampling techniques. In this study, were 30 items on the performance scale and 32 on the transformational leadership scale. Researchers used the Pearson Product Moment correlation method. This study says that both variables have a positive correlation. Performance and Transformational Leadership performed normality and linearity testing using IBM SPSS Statistics 25. These two variables get a correlation coefficient 0.209 with a significant value of 0.015 (P<0.05). The higher the performance, the higher the Transformational Leadership, and vice versa, the lower the performance, the lower the Transformational Leadership of a person.